2022
DOI: 10.1186/s12904-022-01086-0
|View full text |Cite
|
Sign up to set email alerts
|

Advance care planning for patients with cancer and family caregivers in Indonesia: a qualitative study

Abstract: Background Individuals’ willingness to engage in advance care planning is influenced by factors such as culture and religious beliefs. While most studies on advance care planning in Asia have been performed in high-income countries, Indonesia is a lower-middle-income country, with a majority of strongly collectivist and religiously devout inhabitants. We studied the perspectives of Indonesian patients with cancer and family caregivers regarding advance care planning by first exploring their exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
1
7
1
Order By: Relevance
“…Several predisposing, not easily modifiable, factors and barriers related to ACP uptake in the cancer care context were identified. Recent studies highlighted the roles of cultural, and religious factors and the need to consider minority groups’ preferences when assessing the appropriateness of ACP [16,18–22]. These findings are in line with those of a recent review of ACP uptake among older adults with cancer [13 ▪▪ ].…”
Section: Advance Care Planning Uptake-predisposing Factors and Barrierssupporting
confidence: 76%
See 2 more Smart Citations
“…Several predisposing, not easily modifiable, factors and barriers related to ACP uptake in the cancer care context were identified. Recent studies highlighted the roles of cultural, and religious factors and the need to consider minority groups’ preferences when assessing the appropriateness of ACP [16,18–22]. These findings are in line with those of a recent review of ACP uptake among older adults with cancer [13 ▪▪ ].…”
Section: Advance Care Planning Uptake-predisposing Factors and Barrierssupporting
confidence: 76%
“…Thirty-eight studies [15–52] and three reviews were identified [6 ▪ ,8 ▪▪ ,13 ▪▪ ]. Studies were heterogeneous in terms of cancer care contexts, population size and characteristics, research designs, and assessment methods (Table 1).…”
Section: Literature Search and Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Our study showed that three quarters of the participants wished to be informed about their illness by their physicians rather than by family caregivers. Whereas family caregivers in a previous study considered mediated information provision to be a sensitive way of delivering bad news, 17 the majority of cancer survivors in the current study preferred information provision not to be mediated. A minority wished to be informed about their estimated life expectancies.…”
Section: Discussioncontrasting
confidence: 56%
“…First, D.M., J.A.C.R., C.C.D.v.d.R., and A.v.d.H. developed a questionnaire (Data Supplement) on the basis of previous systematic reviews on ACP in Asia, 2 , 3 qualitative studies in Indonesia, 6 , 17 and a cross-sectional survey of the Dutch general population. 18 The questionnaire was translated from English into Bahasa, the main Indonesian language.…”
Section: Methodsmentioning
confidence: 99%